Do you Facebook? Usage and applications of Facebook page among academic libraries in Malaysia / A. R. Riza Ayu and A. Abrizah - A. R., Riza Ayu; A., Abrizah (2011)
This paper explores usage and application of Facebook among Malaysian academic libraries in order to provide academic libraries with ideas for best practices in using social networking sites to better profile themselves and communicate effectively with their users in this new milieu. The research questions guiding this study are as follows: (a) What are the extent and nature of institutional Facebook use by Malaysian academic libraries?(b) What information that Malaysian academic libraries deliver through Facebook page? This study employs content analysis to examine current uses of the library Facebook page. A checkpoint was developed to analyze the libraries' usage and application of Facebook page. A total of 14 academic libraries in Malaysia are using Facebook page as part of their services to users. However only 3 libraries are fully utilizing their Facebook page and they have been identified as —Sitters" based on the 8-S Framework of Category Development for Facebook user. Most libraries are using their Facebook page for marketing and creating awareness of library services to their users. Keywords: Facebook, Malaysia; Social Networking Sites (SNS); Web 2.0; Academic Libraries, Malaysia; Library and information science (LIS, Malaysia.